2010
DOI: 10.1371/journal.pone.0013412
|View full text |Cite
|
Sign up to set email alerts
|

P130Cas Src-Binding and Substrate Domains Have Distinct Roles in Sustaining Focal Adhesion Disassembly and Promoting Cell Migration

Abstract: The docking protein p130Cas is a prominent Src substrate found in focal adhesions (FAs) and is implicated in regulating critical aspects of cell motility including FA disassembly and protrusion of the leading edge plasma membrane. To better understand how p130Cas acts to promote these events we examined requirements for established p130Cas signaling motifs including the SH3-binding site of the Src binding domain (SBD) and the tyrosine phosphorylation sites within the substrate domain (SD). Expression of wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 39 publications
3
54
1
Order By: Relevance
“…Utilizing p130 Cas SH3 domain deletion mutants, studies indicated that this domain and its interaction with FAK are necessary for phosphorylation and the localization of p130 Cas to focal adhesions (FAs) . More recent studies, further explored the temporal and spatial involvement of p130 Cas in FA dynamics and showed the influence of p130 Cas in FA turnover and controlling the migratory response (Donato et al 2010;Meenderink et al 2010). The p130 Cas SH3 domain was shown to be necessary for tyrosine phosphorylation of the SD and the promotion of cell migration (Donato et al 2010), in conditional FAK-deficient mammary tumor cells a reduction in the phosphorylation of Y249 within the p130 Cas SD was observed (Provenzano et al 2008).…”
Section: The Sh3 Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing p130 Cas SH3 domain deletion mutants, studies indicated that this domain and its interaction with FAK are necessary for phosphorylation and the localization of p130 Cas to focal adhesions (FAs) . More recent studies, further explored the temporal and spatial involvement of p130 Cas in FA dynamics and showed the influence of p130 Cas in FA turnover and controlling the migratory response (Donato et al 2010;Meenderink et al 2010). The p130 Cas SH3 domain was shown to be necessary for tyrosine phosphorylation of the SD and the promotion of cell migration (Donato et al 2010), in conditional FAK-deficient mammary tumor cells a reduction in the phosphorylation of Y249 within the p130 Cas SD was observed (Provenzano et al 2008).…”
Section: The Sh3 Domainmentioning
confidence: 99%
“…More recent studies, further explored the temporal and spatial involvement of p130 Cas in FA dynamics and showed the influence of p130 Cas in FA turnover and controlling the migratory response (Donato et al 2010;Meenderink et al 2010). The p130 Cas SH3 domain was shown to be necessary for tyrosine phosphorylation of the SD and the promotion of cell migration (Donato et al 2010), in conditional FAK-deficient mammary tumor cells a reduction in the phosphorylation of Y249 within the p130 Cas SD was observed (Provenzano et al 2008). These studies uncovered the significance of the Cas SH3 domain in the spatial regulation of Cas protein function and in particular its role for the phosphorylation of the SD of the Cas proteins (as described in the next section).…”
Section: The Sh3 Domainmentioning
confidence: 99%
“…The Cas-family proteins NEDD9 (also known as HEF1 and Cas-L) and p130Cas (also known as BCAR1) are examples of signalling proteins that are recruited to focal adhesions, where they regulate cell migration signals (Cary et al, 1998;Klemke et al, 1998;Fashena et al, 2002;Natarajan et al, 2006;Meenderink et al, 2010;Kong et al, 2011;Baquiran et al, 2013;Bradbury et al, 2014). Both proteins contain a C-terminal focal adhesion targeting (FAT) domain (Arold et al, 2002;Mace et al, 2011), characterised by extensive primary sequence and tertiary structural similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Focal adhesions also provide platforms where extracellular cues are converted into intracellular signals (Schwartz, 2010;Zaidel-Bar et al, 2007). Integrinextracellular-matrix (ECM) binding initiates the tyrosine phosphorylation of focal adhesion proteins such as paxillin, FAK (also known as PTK2) and p130Cas (Crk-associated substrate, hereafter referred to as Cas; also known as BCAR1), which then promotes actin remodeling, actomyosin contraction and focal adhesion turnover (Kawauchi et al, 2012;Meenderink et al, 2010;Parsons, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Individual focal adhesions in fibroblasts have a typical lifespan of ,30 min (Delorme-Walker et al, 2011;Kuo et al, 2011;Meenderink et al, 2010). Both the assembly and disassembly of focal adhesions are reportedly modulated by tyrosine phosphorylation of several focal adhesion proteins including FAK, paxillin and Cas (Geiger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%